Impact of CRM on Customer Satisfaction and Customer Loyalty in Armenian Banks - Harutyunyan, Gor («Տնտեսագետ» հրատ․)
The main purpose of this research is to investigate and identify the potential impact of CRM on customer loyalty and satisfaction in the local market. Many studies have demonstrated the strong relationship between the three, but this research focuses specifically on understanding it in the context of the Armenian market. In addition, the research seeks to provide analysis and empirical evidence to enhance the existing knowledge about CRM in the banking sector, particularly in developing markets like Armenia. To examine the hypothesis presented in the article, a quantitative analysis was organized to collect data from B2C customers in Armenia. Respondents came from almost every Armenian bank, totaling 397 participants. We conducted regression, correlation, and comparative analysis on the collected data to identify patterns and relationships between CRM, customer satisfaction, and customer loyalty. Results reveal a medium level dependence between CRM, customer satisfaction, and customer loyalty in Armenian banks, and the change of one affects the others. Armenian banks are one of the most important sectors of the RA economy, providing financial services to individuals, legal entities, and other institutions. CRM strategies are becoming increasingly important for businesses, including banks, in today's competitive market. Understanding how banks adapt to rapidly changing customer demands and market dynamics is crucial. Maintaining a high level of customer satisfaction and loyalty in the banking industry is a cornerstone for long-term success and sustainability. Therefore, identifying the factors that influence customer satisfaction and loyalty is important for strategic decision-making and improving customer-oriented approach.
Keywords: Finance